Decision making Practices on the Implementation of Curriculum in Community-Based Secondary Schools in Tabora Region, Tanzania - Assey, Ernest S.; Malingumu, Winfrida (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The main purpose of this study was to examine the opinions of educational stakeholders concerning the practices of decision-making on the curriculum implementation in community-based secondary schools in Tabora region in Tanzania. Thirty interviewees took part in the study. A qualitative research methodology was used in the investigation. Purposive sampling was utilised as a method of sampling. Thematic data analysis was used to analyse the data after they had been acquired using a semi-structured interviewing method. Findings found out that most community-based secondary schools used decision-making techniques that did not conform to every step and procedures that needed to be followed in order to make rational decisions about teaching, learning, and evaluation in schools. The findings thus corroborated the main argument of the bounded rationality model of decision-making, which assert that whenever a leader engages in decision-making without adhering to proper procedures starting with problem identification and ending with review and evaluation, the decisions made frequently fail to address the real problems that exist in an organization. Finally, the study makes the following recommendations for Tanzania’s local authorities who are in charge of overseeing the community-based secondary schools: ensure that heads of schools regularly participate in training on school pedagogical leadership; ensure that there is effective monitoring and evaluation of how heads of schools make daily decisions regarding teaching and learning; and ensure that there are effective mentorship programmes in place.